(untitled) (Journal of the College of Basic Education, 2025)
The study aimed to identify the extent to which first grade teachers practice phonological awareness skills in teaching reading from their point of view. The researcher followed the descriptive approach in the research procedures. To achieve the goal, the researcher used the questionnaire as a tool for collecting data, as it consisted of (20) items representing the skills, and (3) were placed for each item. Alternatives, which are (I practice, I practice to some extent, I do not practice), and their validity and reliability were verified, then they were applied to the research sample of (75) male and female teachers, and using appropriate statistical methods, and after analyzing the results, it became clear that (8) Skills practiced by male and female Arabic language teachers in the first grade of primary school. In light of the results, some conclusions were drawn, including the lack of Arabic language teachers’ mastery of phonemic awareness skills when teaching reading. The weak qualification of Arabic language teachers in colleges to master phonemic awareness skills. Then the researcher recommended several recommendations. Among them is holding training courses for Arabic language teachers on phonemic awareness skills, paying attention to the subject of linguistic sounds in colleges and educational institutes from which teachers graduate, and considering it as one of the basic and important lessons.